Asthma patients experience increased symptoms of anxiety, depression and fear during the COVID-19 pandemic. (30th June 2021) - de Boer, Geertje M; Houweling, Laura; Hendriks, Rudi W; Vercoulen, Jan H; Tramper-Stranders, Gerdien A; Braunstahl, Gert-Jan
Population studies showed a decrease in psychological wellbeing during the COVID-19 pandemic. Asthma is associated with a negative effect on anxiety and depression, which might worsen during the COVID-19 lockdown. The aim of the study was to compare fear, anxiety and depression between asthma patients and patients wit hout asthma pre-COVID-19 and during COVID-19 pandemic. This study compares fear, anxiety and depression in asthma patients and controls between pre-COVID-19 and during COVID-19 lockdown with a cross-sectional online survey. Participants were invited to fill out several questionnaires pertaining to fear, anxiety, depression, asthma control and quality of life. Asthma patients (N = 37) displayed, during the course of the pandemic, a clinically relevant increase in anxiety (3.32 ± 2.95 vs. 6.68 ± 3.78; p < 0.001) and depression (1.30 ± 1.15 vs. 3.65 ± 3.31; p < 0.001), according to the hospital anxiety and depression levels (HADS) compared to pre-COVID-19 assessment. This was not seen in controls. Also, asthma patients displayed more anxiety about acquiring COVID-19 disease compared to controls ((5.11 ± 1.99 vs. 3.50 ± 2.79), p = 0.006). Patients with asthma experienced an increase in anxiety and depression levels and were more afraid of acquiring COVID-19 disease compared to controls. Also, patients with asthma were more likely to avoid healthcare facilities due to fear of acquiring COVID-19 disease compared to controls. Therefore, we advise health care workers to address these possible negative effects on mental health by phone or e-consults.